3-D Reconstruction of the Human Ribcage Based on Chest X-Ray Images and Geometric Template Models - Koehler, Christopher; Wischgoll, Thomas; Golshani, Forouzan (IEEE multimedia, 2019)
In order to avoid later stages of lung diseases, preventative methods such as regular preemptive screenings are an absolute necessity. For these screenings, costly methods, such as CT scans, are often times cost prohibitive. X-ray imagery is significantly more cost effective. However, it does not provide a three-dimensional view of the patient’s torso. Hence, this paper describes a technique that, based on a series of geometric template models and two X-ray images of a subject’s chest, creates a patient specific 3-D reconstruction of the ribcage. The 3-D reconstruction helps improve visualization of the chest without needing to use expensive 3-D scanners and can be combined with existing computer-aided disease detection techniques to help with diagnosis.